Colorado water, November/December 2014 - Middleton, Lindsey A., editor; Colorado Water Institute, publisher (Colorado State University. Libraries, 2014)
Newsletter of the Water Center of Colorado State University. Theme: Water conflict, mediation, and facilitation.
The newsletter is devoted to enhancing communication between Colorado water users and managers and faculty at the state's research universities.
Keywords: Water resources development -- Colorado; Water use -- Colorado; Water-supply -- Colorado; Water-supply -- Management -- Colorado